Boaventura de Sousa Santos: El milenio huérfano. Ensayos para una nueva cultura política. Editorial Trotta/ILSA, Madrid, 2005 - Gimeno, Juan Carlos; Martín, Mª Victoria (Foro Interno, 2006)
Sin resumen